Green Economy Factors for Sustainable Economic Development - Amanda, Dian; Haqq, Dicky Satria Ananta; Hwihanus, Hwihanus (CV. Lenggogeni Data Publishing, 2024)
Green Economy is one of the crucial factors in supporting the economic sustainability of a country. This research analyzes factors that can improve the welfare of society in various countries, so that they can contribute to wise financial decision making, effective economic and political management. The factors identified include education in understanding financial economic concepts, and consistent socialization, an active role on the part of the government and supporting regulations and policies, as well as the involvement of the private sector. We conducted research using the Meta Analysis methodology by taking five international journals as a reference base for developing research using the meta analysis method. It is hoped that improving the Green Economy can strengthen stability and sustainable economic growth which will have a positive impact on the country.